PhET Aplication Program: Strategi Menguatkan Pemahaman Siswa pada Materi Listrik DC melalui Pembelajaran Berbantu Lab Virtual - Thoha (Jurnal Pendidikan Madrasah, 2019)
This article aims to improve the understanding of DC electrical material by utilizing the PhET circuit-construction-kit-DC application. Learning activities using the Smartloop method and the utilization of virtual labs to facilitate students to solve the problem of electrical circuit material on the law II Kirchoff, more specifically in the closed circuit two loops that the way of completion is very complex with mathematical counts. From the experience of teaching students in the class XII IPA beginning in the school year 2018/2019 received positive note: 1) DC Electrical Learning assisted by PhET applications can be done through online or offline utilization of the Phet circuit-construction-kit-DC application supported by the Smartloop method, makes solving DC electrical problems easier and simpler; 2) The presentation of learning becomes more meaningful, the use of the Phet circuit-construction-Kit-DC application with the Smartloop method continues to prioritize the mastery of basic concepts, follow the rules/Use the principles or agreements that have been prevalent, and use reasoning. The results showed: a) students are more enthusiastic about learning, with indications of students eager to teach their peers who still do not understand the learning process in class and have fun lingering in front of the monitor screen; b) Students are more confident with the learning outcomes, because they can match the results using the usual process and how smartloop and the use of PhET circuit-construction-kit-DC; c) Better learning outcomes.